The Extent of The Impact of Accounting Earnings Management on The Auditor’s Report: A study on a Sample of Companies listed on the Iraqi Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to show the extent of the impact of accounting earnings management on the auditor's report, explain the research problem, and achieve its objectives. The descriptive analytical approach was adopted. Testing the research's hypotheses, Managers resort to using the flexibility available to them in following generally accepted accounting policies and methods to influence net profits. As well as the existence of a direct relationship between the profit management in the company and each of the users' decisions and the auditor's report.